Natural Food Colorants Obtained from Algae and Their Functional Properties - Işıl Ilter; Saniye Akyıl; Mehmet Koç; Figen Kaymak-Ertekin (Turkish Journal of Agriculture: Food Science and Technology)
Colour is one of the major features that fascinate the customers and makes the foods more allurement. Due to changes of customer demands and countries’ legislations, usage of synthetic colorants is being decreased every day and food industry tends to use natural colorant. Algae have recently gained importance owing to a sustainable natural source of colorant. Algae can rapidly increase their biomass compared to plants thus they produce more pigments. This review covers the subjects about the functional properties and usage areas of natural colorants obtained from algae; phycocyanin, phycoerythrin, astaxanthin, canthaxanthin, β-carotene, lutein, fucoxanthin.